2002
DOI: 10.1038/nsb826
|View full text |Cite|
|
Sign up to set email alerts
|

A unique serine-specific elongation factor Tu found in nematode mitochondria

Abstract: The translation elongation factor Tu (EF-Tu) delivers aminoacyl-tRNAs to ribosomes by recognizing the tRNA acceptor and T stems. However, the unusual truncation observed in some animal mitochondrial tRNAs seems to prevent recognition by a canonical EF-Tu. For instance, nematode mitochondria contain tRNAs lacking a T or D arm. We recently found an atypical EF-Tu (EF-Tu1) specific for nematode mitochondrial tRNAs that lack the T arm. We have now discovered a second factor, EF-Tu2, which binds only to tRNAs that … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
53
0

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 49 publications
(53 citation statements)
references
References 27 publications
0
53
0
Order By: Relevance
“…In Caenorhabditis elegans mitochondrial EF-Tu2, a Val (Val 258 ) is found at the position of this threonine. This valine possibly contributes to the strong affinity of EF-Tu2 toward Ser-tRNAs (48). Variations in the amino acid composition of the ␤7, ␤8, and ␤14 strands may therefore explain the relative specificity of each factor toward the various aminoacyl moieties attached to tRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…In Caenorhabditis elegans mitochondrial EF-Tu2, a Val (Val 258 ) is found at the position of this threonine. This valine possibly contributes to the strong affinity of EF-Tu2 toward Ser-tRNAs (48). Variations in the amino acid composition of the ␤7, ␤8, and ␤14 strands may therefore explain the relative specificity of each factor toward the various aminoacyl moieties attached to tRNAs.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, gene content is certainly affected by the ability of exchange of genetic material between the mitochondrial and nuclear compartments, the permeability and/or the presence of specific carriers on the mitochondrial membranes, gene dispensability and the difference in multimeric structure of the respiratory chain complexes between organisms. The secondary structure and size of transfer RNAs (tRNAs) and rRNAs are related to peculiarities of the mitochondrial translational apparatus, as demonstrated in nematodes by the concomitant unusual structure of mt tRNA, ribosomal RNAs (rRNA) and elongation factors (Okimoto and Wolstenholme, 1990;Okimoto et al, 1994;Sakurai et al, 2001Sakurai et al, , 2006Ohtsuki et al, 2002). The number, size and location of non-coding regions is mostly related to the presence of replication and transcription regulatory signals, although the overlap between regulatory signals and coding sequences cannot be excluded in the compact metazoan mtDNA (Valverde et al, 1994;Peleg et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…However, unusual truncations detected in some animal mitochondrial tRNAs appear to prevent recognition via a canonical EF-Tu [33]. Also, it was previously demonstrated that the chromadorean nematode harbors two distinct EF-Tus, one of which (EF-Tu1) binds only to T-armless aminoacyl-tRNAs, whereas the other (EF-Tu2) binds to D-armless Ser-tRNAs [33,34]. Neither of the EF-Tus can bind to canonical cloverleaf tRNAs.…”
Section: Discussionmentioning
confidence: 99%